A high throughput method for isolation of plasmatocytes from hemolymph of adult Drosophila - Mansi Yadav; Jassika Gupta; Debalina Chatterjee; Parul Mittal; Anju Shrivastava; Namita Agrawal (PLoS ONE, 2025)
Macrophages are essential innate immune system components, exhibiting diverse functions crucial for disease prevention. While much is known about their role in innate immunity, studying their functional versatility remains a challenge. Drosophila serves as an excellent model for investigating innate immune signaling due to parallels with vertebrate macrophages. Despite extensive research on larval plasmatocytes, there is a lack of sufficient published literature on adult plasmatocytes, hindering understanding of their contribution to late-onset diseases and aging. Current hemolymph extraction protocols from adult flies have limitations, making them less suitable for immunology experiments that require consistency and minimal stress on flies. Most established methods involve specialized tools such as nanoinjectors, silica capillary probes, etc. which are arduous and require advanced equipment. Although these approaches overcome some challenges in immune cell research, they remain complex and technically intricate. Here, for the first time, we present a protocol for quick, easy, cost-effective, and systematic isolation of adult Drosophila plasmatocytes by which we achieve nearly 2500 cells. We strongly suggest that this protocol might facilitate studies aiming to elucidate molecular and genetic mechanisms associated with immune response in various ailments enabling the exploration of immune cell dynamics, cell signaling and their role in disease progression.